UJI BAKTERI KOLIFORM TERHADAP MINUMAN RINGAN YANG DIJUAL PEDAGANG KAKI LIMA DI KAWASAN MALIOBORO DENGAN METODE MOST PROBABLE NUMBER - Lilis Suryani (LP3 UMY, 2015)
Research on the existence ofcoliform bacteria in the drinks sold by streetvendors in Malioboro area was conducted to measure the amount ofthe bacteria in Es Drrwet (a sort of Javanese traditional drink). Il is an observation and also a laboralory lest. The research population are randomly picked, with 20 out oI30 street-vendors were used as samples. To counl the total number ofthe bacteria a laboratory lest was underlaken employing the method of Most Probable Number